SOCIALIZATION OF DIGITAL TELEVISION BROADCAST TECHNOLOGY CONVERSION (STUDY REGARDING THE REPRESENTATION OF DIGITAL TELEVISION BROADCAST TECHNOLOGY IN OMNIBUS SHORT FILM) - Andre Perbawa; Sunarto, Sunarto; Nandang Mulyasantosa (Bajang Institute, 2024)
Omnibus Short Films are a collection of several short films that have the same theme. Omnibus Short Film with the Theme Migrasi TV Analog / Omnibus STB consists of 4 (four) Short Films entitled : TV Ini Kubelikan Untuk Anakku Tapi Istriku Marah-Marah, Ningali TV, Mbayar and Menjarah. This research uses the Social Reality Construction Theory which is a theory from Peter L. Berger and Thomas Luckmann (1966). This research method uses the Charles Sanders Pierce Semiotic Method, to research and analyze film texts. Apart from that, the researcher also carried out communication interactions with various sources, observations, interviews, documents and other materials as evidence or proof, related to the Socialization of Digital Television Broadcast Technology Conversion (Study Regarding the Representation of Digital Television Broadcast Technology in Omnibus Short Films). The paradigm used in this research is constructivist. This research uses a qualitative approach which allows researchers to discuss the research in more depth. The novelty or novelty of this research is the Omnibus Short Film with the Theme Migration of Analog TV / Omnibus STB, as a medium for conveying messages to the public, has shown that the film is able to make the circulation of information through the socialization of the conversion of digital television broadcast technology, faster and evenly distributed in efforts to socialize the conversion of digital television broadcast technology. This means that it has completed Peter L. Berger's Social Reality Construction Theory, namely that all this time Peter L Berger never talked about the media, but then it was the media that led to representation. So the media plays a role as a construction and representation of reality, in the socialization of the conversion of digital television broadcast technology